Expert perceptions of the popular baby boomer image. (19th July 2013) - Tavener, Meredith; Byles, Julie; Loxton, Deborah
<x xml:space="preserve">Abstract</x> Aim This paper explored how gerontology experts described baby boomers, whether they challenged the popular image, and if they provided alternatives to the popularly reported baby boomer behaviours and characteristics. Methods Qualitative interviews were conducted with ten experts from different areas across Australia. The interviews were semi‐structured and guided by a 'sense‐making' approach to explore the baby boomer construct and identify expert narratives that differed from the popularly tendered image. Results The majority of experts were identified as baby boomers and made use of phrases associated with the popular baby boomer image, such as 'cashed up', 'reinventing retirement' and 'sea change'. Lifestyle and wealth were recognised as staple features of the popular image. To a lesser degree, the experts also recognised alternative characteristics and behaviours, including people with disabilities and those who struggle financially. Conclusions Experts appeared to identify with the popular baby boomer label, but not necessarily the accompanying stereotypes.